Preparedness and challenges of the new normal: perspectives of Filipino students in virtual learning - Vitales, Venus A.; Aquino, Karen Jann M.; De Leon, Emily F.; Lacap, Paz P.; Maranan, Shiela S.; Duldulao, Jamaica J. (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic greatly affected the education sector in the Philippines. From the traditional face to face classroom teaching-learning, schools shifted to flexible learning and virtual classrooms; where learners and educators need to hurdle numerous difficulties such as resources, curriculum revisions and problems in internet connectivity. This is a major concern because the Philippines ranked 77 among the countries with the slowest and least stable Internet connection in the world. This collaborative research among different colleges and universities in the Philippines explored the prevailing concerns of virtual classroom learning to come up with a program that benefits learners and educators in the country. Utilizing descriptive-correlational design, an online survey using Google Form was conducted in the respondent schools after the implementation of virtual learning. A total of 2,444 students from different levels, private and government schools with varying age and sex participated through snowballing data gathering technique. Results revealed that the respondents’ considered themselves physically prepared; but they are not psychological-emotionally and financially prepared in their virtual classroom learning. The students experienced challenges in terms of teacher, curriculum and resources factors. The students perceived that most teachers are unaware that learners differ in terms of capabilities in online learning; thus, they prefer a student-friendly curriculum; and they suggested that the capability of students to have appropriate gadgets and internet connectivity should be looked into by the educators. Significant differences were established between the profile characteristics and preparedness and challenges experienced by the students in their virtual classroom learning. Furthermore, the preparedness and challenges experienced in virtual learning of the respondents are significantly correlated. A proposed program that benefits the students and educators was designed as an output of this research which is recommended for implementation in government and private schools in the Philippines.